Understanding the Impact of PSAK 115 and Financial Distress on Dividend Policy: Evidence of Audit Quality as a Moderator - Rahma Rizka Resita; Made Sudarma; Sari Atmini (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to examine the effect of PSAK 115 implementation and financial distress on dividend policy. As well as testing the role of audit quality in moderating the effect of the implementation of PSAK 115 and financial difficulties on dividend policy. Methodology/approach: This study uses purposive sampling technique, with a total of 103 different companies selected during the period 2016-2023. The data used is secondary data obtained from the company's financial statements. The data analysis techniques used in this study are panel data regression and Moderated Regression Analysis (MRA). Results: The results of the regression analysis show that dividend payments can be significantly affected by the implementation of PSAK 115 and financial difficulties. The results also show that audit quality strengthens the relationship between the implementation of PSAK 115 on dividend payments, however audit quality is unable to strengthen the relationship between financial distress and dividends. Practical implications: The results of this study provide empirical evidence on the implications of type 1 agency theory and signaling theory, especially from industries that on average experience a decline in dividend payout ratios due to current trends and new developments that have an impact on dividend payment policies. Originality/value: This study uses audit quality as a moderating variable which in previous studies has been widely used as an independent variable. This study also uses the dividend payout ratio to explain the impact of agency costs on the implementation of PSAK 115 and financial distress.